Analisis Tujuan Membaca Mahasiswa Semester 1 Program Studi Pendidikan Bahasa dan Sastra Indonesia - Wulandari, Dewi; Fauzan, Iqbal Husni; ZA, Mahmudah Fitriyah (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2024)
The research aims to analyze reading interest, as well as what interests require first semester students majoring in Indonesian Language and Literature Education to read. This research was conducted using a qualitative descriptive method, which focuses on problems based on facts that are carried out by observing or observing. As for data collection, it was carried out using a questionnaire which was then filled in by 1st semester PBSI students, after the data was collected, the researchers analyzed the data. From the results of data analysis, the average interest in reading of 1st semester PBSI students is around 75%-80%. In fostering interest in reading, someone must expect something from what is read, one of which is someone's purpose for reading. For this reason, in the variation of reading purposes, the majority of students (37.5%) have the purpose of reading to find information about a term or obtain information compared to other variations of reading purposes. By reading they can achieve what they want to achieve after reading, students have hopes of obtaining information to increase insight. Reading is also expected to foster inspiration, increase creativity, and provide new input related to new topics that need to be learned, besides that reading can also be a means of entertainment.